Extrapolation of In Vivo Hepatic Clearance from In Vitro Uptake Clearance by Suspended Human Hepatocytes for Anionic Drugs with High Binding to Human Albumin: Improvement of In Vitro-to-In Vivo Extrapolation by Considering the “Albumin-Mediated” Hepatic Uptake Mechanism on the Basis of the “Facilitated-Dissociation Model” - Kim, Soo-Jin; Lee, Kyeong-Ryoon; Miyauchi, Seiji; Sugiyama, Yuichi (Drug metabolism and disposition, 2019)
We investigated whether human serum albumin (HSA) in suspended human hepatocytes would affect the uptake clearance of anionic drugs with high binding to HSA and improve the extrapolation of in vivo hepatic clearance from in vitro uptake clearance by the hepatocytes via the “albumin-mediated” hepatic uptake mechanism. The uptake clearances for total forms (PSinf) and for unbound forms (PSu,inf) of 11 anionic drugs [all of which were organic anion-transporting polypeptide (OATP) substrates] were determined with suspended human hepatocytes in varying concentrations of HSA. The fraction of unbound drugs (fu) was determined using an equilibrium dialysis at the various HSA concentrations. The PSinf values decreased with increasing concentrations of HSA, whereas the unbound uptake clearances (PSu,inf(+) = PSinf/ fu) in the presence of HSA increased substantially, thus demonstrating the “albumin-mediated” hepatic uptake mechanism. The relationships between PSinf and HSA concentration were well described by the previously proposed facilitated-dissociation model, in which the drug–albumin complex interacts with the cell surface, enhancing the dissociation of the complex and providing unbound drug for hepatic uptake. Furthermore, the PSu,inf (+) values in in vivo conditions (at 5% HSA) were predicted from those obtained in isolated hepatocytes on the basis of the facilitated-dissociation model, revealing compatibility with the overall hepatic intrinsic clearance in vivo. We conclude that the “facilitated-dissociation” model is useful for describing the “albumin-mediated” hepatic uptake phenomenon of OATP drugs and to predict hepatic uptake clearance in vivo.